1999
DOI: 10.1097/00005392-199909000-00104
|View full text |Cite
|
Sign up to set email alerts
|

Staghorn Calculi in Children

Abstract: ESWL using the Siemens Lithostar-ULTRA is simple, effective and safe primary treatment in children with staghorn calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[2] Our group recently reviewed results of 149 pediatric patients treated with a single session of ESWL at multiple community and academic centers in the Midwestern US and found a 71% stone-free rate. [6] In other pediatric series, ESWL has been demonstrated to be successful in treating large stones (20-30 mm), with a 95% stone-free rate,[7] staghorn calculi with a 73% stone-free rate[8] and lower-pole calculi with a stone-free rate between 61% and 92%. [79] Thus, the efficacy of ESWL for renal stones in the pediatric population is well established.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Our group recently reviewed results of 149 pediatric patients treated with a single session of ESWL at multiple community and academic centers in the Midwestern US and found a 71% stone-free rate. [6] In other pediatric series, ESWL has been demonstrated to be successful in treating large stones (20-30 mm), with a 95% stone-free rate,[7] staghorn calculi with a 73% stone-free rate[8] and lower-pole calculi with a stone-free rate between 61% and 92%. [79] Thus, the efficacy of ESWL for renal stones in the pediatric population is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Although the application of ESWL in children was first reported in 1986 [15] , ESWL monotherapy for managing staghorn calculi in children was first reported in 1999 by Orsola et al [32] where 11 of 15 children were rendered stone-free. In recently published studies the reported stone-free rates after ESWL increased to 95% for infants and 71–87.5% for children with staghorn calculi [33,34] .…”
Section: Eswl For Staghorn Calculi In Childrenmentioning
confidence: 99%
“…When considering ESWL for kidney stones in children, unlike in PCNL, it appears to be a different condition from that in adults, and recommendations for children cannot be directly inferred from those for adults. This is mainly because staghorn calculi in children represent a smaller stone burden, and that the small body volume of children facilitates better shock-wave transmission, both resulting in superior stone fragmentation and clearance rates [32,34] . In addition, the shorter duration of the disease, greater stone fragility and lower impedance to shock waves might be the possible reasons for better stone fragmentation.…”
Section: Eswl For Staghorn Calculi In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] The incidence of Steinstrasse following ESWL in children without ureteral stents has shown to be very low (significantly lower than for adults). [236] As a result, preoperative stenting is generally reserved for children with solitary kidney, severely obstructing stones, or abnormal anatomy.…”
Section: Extracorporeal Shock Wave Lithotripsymentioning
confidence: 99%